2015
DOI: 10.1111/odi.12355
|View full text |Cite|
|
Sign up to set email alerts
|

Genetic association between VEGF polymorphisms and BRONJ in the Korean population

Abstract: The CC homozygotes of rs2010963 and rs3025039 polymorphisms in the VEGF gene were associated with an increased risk of BRONJ in the Korean population. Further epidemiological cohort studies with a larger sample size would be required to confirm the suggestive correlations.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
15
0
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(17 citation statements)
references
References 24 publications
1
15
0
1
Order By: Relevance
“…We found that the T allele in the asthma group was present in a significantly higher proportion than in the control group. The VEGF rs3025039 SNP is not only associated with asthma (Lachheb et al, 2008); like the VEGF rs3025020 polymorphism, rs3025039 is also associated with other diseases, for example, bisphosphonate-related osteonecrosis of the jaw (Choi et al, 2015) and ovarian cancers (Janardhan et al, 2015). Compared with healthy controls, the frequency of the T allele of rs3025039 is significantly higher in patients with HCH (He et al, 2015).…”
Section: Discussionmentioning
confidence: 99%
“…We found that the T allele in the asthma group was present in a significantly higher proportion than in the control group. The VEGF rs3025039 SNP is not only associated with asthma (Lachheb et al, 2008); like the VEGF rs3025020 polymorphism, rs3025039 is also associated with other diseases, for example, bisphosphonate-related osteonecrosis of the jaw (Choi et al, 2015) and ovarian cancers (Janardhan et al, 2015). Compared with healthy controls, the frequency of the T allele of rs3025039 is significantly higher in patients with HCH (He et al, 2015).…”
Section: Discussionmentioning
confidence: 99%
“…With reference to genetic factors, Choi et al. [68] concluded that the CC homozygotes of rs2010963 and rs3025039 polymorphisms in the VEGF gene were associated with an increased risk of BRONJ in the Korean population. In Japan, many of the risk factors mentioned above for ARONJ has no published evidence to support their importance.…”
Section: Risk Factors For Aronjmentioning
confidence: 99%
“…There are a number of theories regarding the pathogenesis of MRONJ, with varying levels of evidence to support the following as contributing factors: osteocyte apoptosis (Roelofs et al, ); osteoclast suppression (Allen & Burr, ); inhibition of blood vessel formation (Santini et al, ); obstruction of the vasculature (Favia, Pilolli, & Maiorano, ); suppression of soft tissue healing (Reid, Bolland, & Grey, ), impaired immunity (Pazianas, ), genetic risk factors (Choi, Lee, Lee, & Kim, ); and infection or inflammation as a result of oral biofilms (Sedghizadeh et al, ). The role of oral health, and in particular dental extractions, has been extensively reported.…”
Section: Introductionmentioning
confidence: 99%